THE MAINTENANCE OF MANDAILINGNESE LANGUAGE IN TANJUNGBALAI - Nurul Husnah Harahap; Didik Santoso; Anni Holila Pulungan (Universitas Negeri Medan, 2019)
This study deals with the language maintenance of Mandailingnese in Tanjungbalai. It usesqualitative research design. It is conducted descriptively. This study aims to examine the types of language maintenance by Mandailingnese people in Tanjungbalai, find out the ways in maintaining the Mandailingnese language in Tanjungbalai and find out the reasons why the speakers of Mandailingnese people maintain their language in Tanjungbalai. The subjects were 10teenagers (boys and girls) of Mandailingnese. The use of instruments in this study were observation and interview. The observation were used to examine the types of language maintenance by Mandailingnese people in Tanjungbalai in order to describe the ways of Mandailingnese language maintenance. The interview was used to gain the reasons of Mandailingnese language maintainancein Tanjungbalai. The theories of Fasold, Fishman and Holmes are used in this study. The data were analyzed by Miles, Huberman and Saldana (2014). There are four types of language maintenancein Tanjungbalai namely; low maintenance, medium maintenance, strong maintenance and extreme maintenance. There are two ways to maintain Mandailingnese language in Tanjungbalai namely; join the community and teach the language to younger sister/brother. There are four reasons why they maintain their language namely; to express their identity as Mandailingnese people, to achieve self pride as Mandailingnese people, to tell certain issue and to creat closer relationship. Analysis of data clearly indicates that Mandailingnese language maintenance were done in Tanjungbalai.Keyword : language maintenance, reasons for language maintenance, Mandailingnese in Tanjungbalai